PHYTOCHEMICAL AND ANTIBACTERIAL ACTIVITY OF HEXANE AND ETHYL ACETATE EXTRACT OF KNOXIA SUMATRENSIS (RETZ.) DC. - S, LOGANATHAN; K, SELVAM (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The study was carried out the phytochemical and antibacterial activity of Knoxia sumatrensis (Retz.) Dc. using hexane and ethyl acetate extracts. Methods: The phytochemical screening was extracted from hexane and ethyl acetate solvent and its screening was analyzed by standard procedure. GC-MS technique was analyzed in ethyl acetate extract to identify the components present in the extract. The hexane and ethyl acetate extract of the plant was tested for antibacterial activity against human pathogenic bacteria using disk diffusion method. Results: The phytochemical screening was revealed the presence of phenols, saponins, flavonoids, cardiac glycosides, steroids, and tannins. The GC-MS results showed that the presence of seven bioactive compounds in ethyl acetate extract. The major compounds were identified such as N-Hexadecanoic Acid (9.336), 2-Piperidinone, N-[4-Bromo-N-Butyl] - (37. 883). The ethyl acetate extract showed good antibacterial activity. The maximum zone of inhibition was noticed in S. aureus (8.25 mm) using ethyl acetate extracts at 50 μg. Conclusion: Thus, this study the information regarding the phytochemical constituents present in the both extract. Hence, it can be used for further therapeutic applications in the near future study.